2021
DOI: 10.1177/2333794x211022265
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Rome IV Criteria on the Prevalence of Functional Abdominal Pain Disorders and Functional Constipation among Children of the Western Region of Saudi Arabia

Abstract: Functional gastrointestinal disorders are characterized by absence of anatomical and biochemical alterations, and are diagnosed and classified based on symptomatology. We aim to explore the prevalence of functional abdominal pain disorders and Functional constipation using Rome IV criteria. An online questionnaire was distributed randomly via social media targeting the general population of the western region of Saudi Arabia. Parents who have at least 1 child in the age group 3 to 18 years were included. Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 40 publications
(93 reference statements)
0
16
3
Order By: Relevance
“…The prevalence of constipation among children aged 3–18 years in this review (13%) was higher than that reported in a recent publication from the western province of Saudi Arabia using the ROME IV criteria (4.7%) ( 34 ). In general, the prevalence of constipation increases with age regardless of the diagnostic criteria used.…”
Section: Discussioncontrasting
confidence: 80%
“…The prevalence of constipation among children aged 3–18 years in this review (13%) was higher than that reported in a recent publication from the western province of Saudi Arabia using the ROME IV criteria (4.7%) ( 34 ). In general, the prevalence of constipation increases with age regardless of the diagnostic criteria used.…”
Section: Discussioncontrasting
confidence: 80%
“…Further studies are required to evaluate the diagnostic accuracy of the RIV‐QPGS and Rome IV criteria for FAPDs. It is noted that the prevalence of overall FAPDs in our study was lower than the other studies using either Rome III 2–4,18 or Rome IV criteria, 10–12 but higher than the study from Saudi Arabia 17 . This could be differences in life‐style, culture, socio‐economic status, diet and gut microbiome across countries as well as the research methodology.…”
Section: Discussioncontrasting
confidence: 72%
“…9 A recent study from Saudi Arabia has shown the prevalence of FAPDs and FC is 3.1% and 4.7%, respectively. 17 We did not identify non-retentive faecal incontinence in this survey. The result is consistent with the previous meta-analysis which showed the low prevalence of functional non-retentive faecal incontinence (0-1.8%), 8 and the recent systematic review which shows the prevalence of 0-2.6% (mean 0.36%).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations